Mulheres em situação de rua em Cuiabá : algumas reflexões a partir da psicologia social comunitária - Barros, Carine Muller Paes de (2020)
This dissertation discusses the social phenomenon of street women, being held in the central region of the city of Cuiabá-MT. The theoretical framework adopted was that of Latin American Community Social Psychology and Popular Education, including authors such as Maria de Fátima Quintal de Freitas, Silvia Lane, Maritza Montero, Ignácio Martín-Baró, Paulo Freire, among others. The dissertation was divided into four chapters presenting, respectively, the education history of the street population, a bibliographic review of the study and the tracking of field research and the paths taken. The study had a qualitative character, being a participant research. The general objective of this research was to understand the psychosocial dimensions of the street women issue, in the city of Cuiabá, with the following specific objectives: a) characterize the daily survival experiences of street women; b) know the process of subjection to homelessness experienced by these women; c) contribute to the theoretical framework of Community Social Psychology in the work with these women. Such research involved conversations were performed, based on Community Social Psychology, held in the street environment, that have been recorded in audio (later transcribed) and the observations were recorded in field notes to data recording. The data were subsequently analyzed using Bardin's content analysis. Therefore, there were originated these thematic categories: a) suffered violence; b) drug use; c) a street as a shelter and urgency for housing policy; d) strategies to acquire money and subsistence on the streets e) prejudice and discrimination; these categories are discussed until the end of the research. The results found can contribute to the understanding of the psychosocial dimensions that cross the daily life of women living on the streets in Cuiabá.